(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
The study sought to examine the factors that hinder the teaching of computers in four selected secondary schools in Chiwundura Cluster Centre in Gweru in Midlands Province in Zimbabwe. Teaching and learning of computers in educational institutions cannot be over-emphasized the world over, as computers are now the lifeblood of any society. The study adopted a mixed research approach, thus the use of interviews, questionnaires and observations. 20 respondents who are teachers selected using probability sampling method from four (4) selected secondary schools from a pool of 5 secondary schools in the cluster. The findings established that some of the secondary schools in Chiwundura do not have computers hence this problem has contributed much to the non-teaching and learning of computers in Chiwundura secondary schools. The study revealed that lack of trained teachers and poor funding were considered as the major causes to the non-teaching and learning of computers in secondary schools, computer illiteracy, lack of computer usage infrastructure among others were negatively affecting the teaching of computers in selected secondary schools in Chiwundura. The study concluded that teacher training institutions should train more computer teachers for to curb the shortage of trained personnel that are meant for the teaching and learning of computers. In a bid to eliminate the non-teaching and learning of computers, schools’ administrators need to be trained or oriented on how to implement the teaching and learning of computers in secondary schools. The study recommended the stakeholders to resume the computerization and the rural electrification programmes as well as introduce the use of alternative source of power like solar energy. Further recommendations were that administrators in secondary schools in Chiwundura should priorities the implementation of the teaching and learning of computer studies when making their budgets, hence the need for the acquisition and development of computer infrastructure in their schools.